2019
DOI: 10.3892/mmr.2019.9825
|View full text |Cite
|
Sign up to set email alerts
|

Metallic wear debris collected from patients induces apoptosis in rat primary osteoblasts via reactive oxygen species‑mediated mitochondrial dysfunction and endoplasmic reticulum stress

Abstract: Although total hip arthroplasty is considered to be an effective surgical procedure for treating hip joint diseases, it is hindered by implant wear debris, which induces aseptic loosening. Various cell types are involved in this pathogenesis; however, the interactions between wear debris and osteoblasts, which serve a crucial role in bone formation, have not been clearly illustrated. In the present study, minor metallic wear particles were collected from the interfacial membrane around loosened implants of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Consistently, our results indicated that AITC treatment increased ROS generation and the antioxidant NAC exhibited a protective effect against AITC. ROS generation was reported to upregulate GADD153/CHOP expression and induce ER stress-mediated apoptosis (50,51). In line with the findings of previous studies (48,51), our data showed that ROS-induced ER stress signaling was involved in AITC-induced caspase-3-dependent apoptosis in HT-29 cells.…”
Section: Discussionsupporting
confidence: 90%
“…Consistently, our results indicated that AITC treatment increased ROS generation and the antioxidant NAC exhibited a protective effect against AITC. ROS generation was reported to upregulate GADD153/CHOP expression and induce ER stress-mediated apoptosis (50,51). In line with the findings of previous studies (48,51), our data showed that ROS-induced ER stress signaling was involved in AITC-induced caspase-3-dependent apoptosis in HT-29 cells.…”
Section: Discussionsupporting
confidence: 90%
“…When all the torque is concentrated on a smaller contact area versus the entire implant surface, a higher localized stress will result therefrom, which, in turn, can facilitate titanium release in a peri-implant bone [ 46 ]. Wear debris have been assumed to be one of the major factors responsible for aseptic implant loosening [ 47 ]. The real effects of metal and surface contaminant release in the osseointegration process are not yet fully understood, even though it is reported as a possible disturbing factor for bone remodeling balance and severe inflammatory and allergic reactions [ 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, multiple studies have proven that chitosan and its derivatives have various antioxidant properties [ 28 ]. Yang et al placed wear particles obtained from the interface membrane around a patient’s sterile loosening prosthesis into the primary osteoblasts of rabbits and found that the increased production of reactive oxygen species can induce osteoblast apoptosis [ 29 ]. The specific mechanism is that active oxygen mediates osteoblast apoptosis through the mitochondrial apoptotic protease-dependent pathway and the endoplasmic reticulum stress pathway, and this apoptosis can be attenuated by antioxidant antagonistic effects.…”
Section: Discussionmentioning
confidence: 99%